PENINGKATAN MOTIVASI BELAJAR BAHASA INDONESIA MELALUI PEMBELAJARAN BERBASIS PORTOFOLIO SISWA KELAS IV SDN KEBONSARI 01 KEC. KEBONSARI MADIUN TAHUN PELAJARAN 2011/2012 - Muchsin Muchsin (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2015)
Some linguists argue about the definition of reading, WJS Poerwodarminto (1976: 71) says that reading is seen while express an article with the aim to determine its contents. Another opinion expressed by Kastowo (1978: 1) that reading is catching an understanding through writing. Based on the above opinion, the reading reveals not only writing but also understanding the text. The formulation of this research as follows: "Is there an ability increasing to understand the rather long text (150-200 words), manual guide, the meaning of words in a dictionary / encyclopedia through portfolio learning model of the second semester of the fourth grade students of SDN Kebonsari 01 Madiun in the Schooling Year 2011/2012? "study, researchers collaborate with other teachers and the principals. Researchers involved in the study from the beginning to the end of the study. Researcher is trying to see, observe, feel, live, reflect and evaluate learning activities. The stages of research consist of planning, acting, observing and reflecting. The study collected data were statistically analyzed using the formula that is mean or average to get accurate results. From the analysis and observations on this study and refers to the hypothesis can be concluded that: there is an increased ability to understand the text rather long (150-200 words), manual guide, the meaning of words in a dictionary / encyclopedia through cooperative learning model of fourth grade students of SDN 01 Kebonsari in the Schooling year 2011/2012.